MENINGKATKAN KUALITAS BACAAN AL-QUR’AN MELALUI METODE TALAQQI SISWA/I MTs TAHFIDZUL QUR’ANDI CILENDEK BOGOR - Siti Sumiati; H. Fahmi Irfani; H. Kamalludin (CV. ADIBA AISHA AMIRA, 2023)
This article discusses to improve the quality of the Qur'an reading through the Talaqqi Method of Class VII and VIII Students in MTs Tahfidzul Quran Cilendek Bogor. Bogor City, West Java Province. The purpose of this study was to improve the quality of the Qur'anic reading through the Talaqqi Method of Class VII and VIII Students in MTs Tahfidzul Quran Cilendek Bogor. Bogor City, West Java Province. This research is a classroom action research. The subjects of this study were students of class VII and VIII in MTT Tahfidzul Quran Cilendek Bogor, while the object of research was the leading of the Talaqqi method in improving the quality of short surahs from the Qur'an of students/I class VII and VIII MTs Tahfidzul Qur'an Cilendek Bogor. The results of this study can be concluded that the reading activity of the Koran through the Talaqqi method can improve the quality of reading the Koran of students, this can be seen in each cycle. In the pre-cycle the average results of students' reading ability of the Koran of 61 with the incomplete category, and only 15 students out of 30 students reached an average score. After the action of the first cycle of the Quality of the Koran, students rose to 75 in this cycle, it was categorized as approaching complete but there were several students who had increased with the number of students complete as many as 20 students and 10 students were still incomplete. In cycle II the ability to read the Koran students experienced a significant increase with an average score of 85.02 with a complete category, with a total number of students who were complete as many as 24 students and 6 other students approached completeness